ICT resources for research: an ANOVA analysis on the digital research skills of higher education teachers comparing the areas of knowledge within each gender - Guillén-Gámez, Francisco David; Ruiz-Palmero, Julio; Sánchez-Rivas, Enrique; Colomo-Magaña, Ernesto (My University, 2020)
Research skills are part of the academic activities of Higher Education teachers. Regardless of the knowledge area they teach, there is a need to observe, reflect, select, analyse and communicate scientific results using technological advances. The aim of this study is to analyse the use that teachers make of different ICT resources for research in terms of gender, comparing within each gender the different areas of knowledge to which the teachers belong (Science and Engineering-Architecture, Health Sciences, Art-Humanities and Social-Legal Sciences). To this end, an ex post facto design through surveys was used with a sample of 867 university teachers in the Spanish education system. For the comparative analysis, univariate ANOVA by multiple comparisons was used. The findings revealed that teachers have, in general terms and in both genres, an average level of use, highlighting more use in digital databases, academic Google, high-impact journal websites, and very little use in data analysis software, mainly in qualitative software. The results highlighted that the EngineeringArchitecture area is the one that makes the greatest use of ICT for research in comparison with the Art-Humanities area which uses ICT resources the least. The results demonstrate the need to develop procedural and cognitive skills in teaching staff in the most needed areas, not only to encourage them to continue researching and sharing the results acquired, but also to attend and prepare students in research skills so that they can continue learning and increasing their academic and professional training once the university stage is over.
Keywords: Teaching staff; Higher education; Use; Digital research skills; ICT resources; Areas of knowledge; Gender